2019
DOI: 10.1103/physreve.100.043101
|View full text |Cite
|
Sign up to set email alerts
|

Pore-scale velocities in three-dimensional porous materials with trapped immiscible fluid

Abstract: We study and document the influence of wetting and nonwetting trapped immiscible fluid on the probability distribution of pore-scale velocities of the flowing fluid phase. We focus on drainage and imbibition processes within a three-dimensional microcomputed tomographic image of a real rock sample. The probability distribution of velocity magnitude displays a heavier tail for trapped nonwetting than wetting fluid. This behavior is a signature of marked changes in the distribution and strength of preferential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…This assumption is valid because of the low flow rate Q used, which also prevents the deformation and displacement of air bubbles. Guédon et al (2019) found no differences in the velocity distributions for slip and no-slip boundary conditions between wetting and non-wetting phases. Triadis et al (2019) found the transport behavior is the same for slip and no-slip boundary conditions between water and air phase.…”
Section: Flow Within the Liquid Phasementioning
confidence: 67%
“…This assumption is valid because of the low flow rate Q used, which also prevents the deformation and displacement of air bubbles. Guédon et al (2019) found no differences in the velocity distributions for slip and no-slip boundary conditions between wetting and non-wetting phases. Triadis et al (2019) found the transport behavior is the same for slip and no-slip boundary conditions between water and air phase.…”
Section: Flow Within the Liquid Phasementioning
confidence: 67%
“…Here, we present Steady-State (SS) two-phase coreflooding experiments (Moghadasi et al, 2015) as well as the methodology for the evaluation of two-phase relative permeabilities based on the use of porescale simulations (Guédon et al, 2019). We also describe the technique for the synthetic generation of heterogeneous fields (see Section 2.3) employed in our reservoir simulations.…”
Section: Methodsmentioning
confidence: 99%
“…When considering the results of direct pore-scale two-phase flow simulations (i.e., our numerical approach), we evaluate uncertainties on reservoir model input parameters through a standard Maximum Likelihood (ML) framework grounded on results from computational fluid dynamics (CFD) simulations on three-dimensional (3-D) models (Guédon et al, 2019).…”
Section: Figure 1-sketch Of the Workflow Of The Analysis (N Correspomentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the particles' kinetic probability distribution in real porous media is essential to achieve particulate control 8,9 . Prior studies described how such distributions depend on pore structural variables (e.g., obstacle size 10 , porosity [11][12][13] , pore structure 14 ) by fitting the probability data into standard probability distribution functions (PDFs), such as exponential 10,15,16 , stretched exponential 11,17 , power-law 14,18 , and power-exponential ones 12 . However, the assessment of their predictive ability remains elusive, because these functions contain fitting parameters that often lack a solid physical foundation.…”
mentioning
confidence: 99%